Correlation Between Maternal Age and gestational Age with Hypertension Gestational in Denpasar City - Ketut Novia Arini (Politeknik Kesehatan Kartini Bali, 2021)
Hypertension is one of the causes of maternal mortality in Indonesia. If hypertension in pregnancy is not treated properly, it can cause harm to both the mother and the fetus. One of the consequences that can result from the occurrence of hypertension in pregnancy is stunted fetal growth which can lead to low birth weight, premature birth, placental abruption, and cardiovascular disease (Adrian, 2021). The purpose of this study was to determine the relationship between maternal age and gestational age on the incidence of hypertension in pregnant women. This research is an explanatory research that is looking for an explanation of the relationship between independent and dependent variables, with a cross-sectional design. The sample selection in this study used a purposive sampling method with a total sample of 460 respondents. Based on the results of the study, from 460 respondents, 340 people (73.9%) were in the age range of 20-35 years. A total of 282 people (61.3%) were in the third trimester of pregnancy. As many as 50 pregnant women (10.9%) had hypertension. There is a relationship between maternal age and gestational age on the incidence of hypertension in pregnant women with p value <0.05.